Peran Madrasah Dalam Menerapkan Sistem Pembelajaran Full Day School untuk Meraih Siswa Berprestasi Tingkat Nasional di Madrasah Aliyah Darussalam Boarding School Samarinda - Ismail Ismail; Wildan Saugi (Journal on Education, 2024)
Globalization presents both threats and opportunities for teenage students. Threats arise from the negative impacts of globalization, while opportunities come from the development of academic potential. Full-day school directs students towards positivity and avoids the troubling hedonistic culture. This research aims to explore the role of a madrasah implementing the full-day school learning system in producing nationally accomplished students. It is a qualitative study conducted at MA Darussalam Boarding School in Samarinda. Primary data sources include the madrasah head, curriculum vice principal, student affairs vice principal, and students. Secondary data sources consist of supporting documents necessary for the research. Data collection techniques involve observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, encompassing data collection, reduction, presentation, conclusion drawing, and verification. Based on the research findings, the full-day school system provides space for the madrasah to innovate and offer additional programs to support students in achieving national-level excellence. Efforts include motivating students, conducting public speaking training, organizing extracurricular activities based on interests and potentials, providing guidance for students participating in competitions from regional to national levels, forming MTQ competition communities, a teacher team seeking competition information, and most importantly, the madrasah implementing a one-student-one-achievement program.